Competências coletivas e capital social na cadeia produtiva de morangos na região do Vale do Caí-RS - Pistore, Adriano (My University, 2014)
The themes of social capital and collective competences are related by addressing the social and economic development organizations in a network perspective. Social capital refers to features of social organization such as networks, norms and trust that facilitate coordination and cooperation for mutual benefit. The ability to relate to and cooperate with other individuals in an organization, or between organizations, is considered a responsibility of the individual. However, it is through the skill developed by groups of individuals to perform tasks that generate collective way up the collective competences. In this sense, this research seeks to analyze the dynamics of collective competences in order to understand how the contextual characteristics of social capital may favor the consolidation of these skills in agricultural production of small fruits, in this case the supply chain of strawberries in the Caí Valley. As research methodology was used exploratory research with qualitative, using questionnaires as a data collection tool. The study population was composed of the main links in the supply chain, along with representatives of the environment organization. The research identified the attributes of collective skills, their training and development, characterize the elements that define and analyze social capital and how these approaches together can offer support and coordination necessary to provide a different understanding about the production process of strawberry. The main results are the existence of collective meaning and, consequently, of the interdependence between the links of the supply chain, strongly promoted by elements of social capital.The themes of social capital and collective competences are related by addressing the social and economic development organizations in a network perspective. Social capital refers to features of social organization such as networks, norms and trust that facilitate coordination and cooperation for mutual benefit. The ability to relate to and cooperate with other individuals in an organization, or between organizations, is considered a responsibility of the individual. However, it is through the skill developed by groups of individuals to perform tasks that generate collective way up the collective competences. In this sense, this research seeks to analyze the dynamics of collective competences in order to understand how the contextual characteristics of social capital may favor the consolidation of these skills in agricultural production of small fruits, in this case the supply chain of strawberries in the Caí Valley. As research methodology was used exploratory research with qualitative, using questionnaires as a data collection tool. The study population was composed of the main links in the supply chain, along with representatives of the environment organization. The research identified the attributes of collective skills, their training and development, characterize the elements that define and analyze social capital and how these approaches together can offer support and coordination necessary to provide a different understanding about the production process of strawberry. The main results are the existence of collective meaning and, consequently, of the interdependence between the links of the supply chain, strongly promoted by elements of social capital.
Os temas capital social e competências coletivas estão relacionados por tratarem do desenvolvimento econômico e social de organizações sob uma perspectiva de rede. Capital social refere-se a aspectos da organização social, tais como redes, normas e confiança, que facilitam a coordenação e a cooperação para benefício mútuo. A habilidade de relacionarse e cooperar com os demais indivíduos de uma organização ou entre organizações é considerada uma competência do indivíduo. Porém, é através da habilidade desenvolvida por grupos de indivíduos de realizar tarefas de modo coletivo que geram-se as competências coletivas. Neste sentido, esta pesquisa buscou analisar a dinâmica das competências coletivas no intuito de entender de que forma as características contextuais do capital social podem favorecer a consolidação dessas competências na produção agrícola de pequenas frutas, neste caso a cadeia produtiva de morangos do Vale do Caí-RS. Como metodologia de pesquisa, foi utilizada a pesquisa exploratória, com caráter qualitativo, utilizando questionários como ferramenta de coleta de dados. A população estudada foi composta pelos principais elos da cadeia produtiva, juntamente com representantes do ambiente organizacional da cadeia. A pesquisa permitiu identificar os atributos das competências coletivas, sua formação e desenvolvimento, caracterizar os elementos que definem o capital social e analisar como estas abordagens em conjunto podem oferecer a sustentação e a articulação necessárias para proporcionar um entendimento diferenciado sobre o processo de produção do morango no Vale do Caí. Entre os principais resultados encontram-se a existência de sentido coletivo e, consequentemente, de uma interdependência entre os elos da cadeia produtiva, fortemente promovidos por elementos do capital social.
Keywords: Comportamento organizacional; Capital social; Morango - Cultivo - Vale do Caí, Região (RS); Agricultura; Agriculture; Social Capital